(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
The Indonesian film industry has experienced significant growth in recent years, but on the other hand, it also faces serious challenges due to the widespread illegal access to films through pirated streaming websites. This study aims to analyze Indonesia’s positive legal framework concerning such illegal access practices and evaluate the effectiveness of law enforcement in protecting intellectual property rights in the digital era. This research employs a normative juridical method with a qualitative descriptive approach, based on the study of legislation, jurisprudence, and relevant legal literature. The findings indicate that although Indonesia has legal instruments such as Law No. 28 of 2014 on Copyright and Law No. 11 of 2008 on Electronic Information and Transactions, the implementation and enforcement of these laws still face various obstacles. The phenomenon of pirated websites is not only driven by weak supervision and legal sanctions, but also by low public awareness and changes in film consumption patterns due to technological advancements. Therefore, a legal approach that is not only repressive but also preventive and educational is necessary to create more effective protection of copyright in the national film sector.